A Study on Farmers Preference and Market Promotion Activities with Reference to Rice Herbicides - Sivakumar, K.; Sivakumar, S.D. (Indian Journal of Marketing, 2004)
The major objective of discovering and using herbicides has been to replace the arduous, backbreaking manual weeding and also to save time required for performing weeding operations. Ever rising wages and fuel costs have also necessitated the farmers to switch over to herbicides for controlling weeds. Use of herbicides has got its own advantages. Herbicides could control weeds even before they emerged. In broadcast sown and narrow row crops, herbicides have been very effective. In wide row crops, herbicide controlled every weed in intra row, without damaging inter crop. It could kill weeds, which resembled the crop, which escaped manual weeding operations. Herbicides could withhold growth of weed for a considerable period after their application. However, the use of herbicides depended on the technical knowledge of the farmer regarding herbicides and their application.